Subjective Experiences of Working as a Healthcare Worker in South Africa: A Qualitative Study - Sounes, Daniela (University of the Witwatersrand, Johannesburg, 2024)
This study explores the perceptions and experiences of healthcare workers (HCWs) in South Africa. The study aims to understand the subjective lived experiences of HCWs, including the systemic issues, working conditions, psychological impacts, sense of purpose, and coping mechanisms of HCWs. Using a qualitative approach, data were collected through open-ended questions via an online survey, resulting in responses from 177 participants across eight of the nine provinces in South Africa. The analysis revealed profound systemic challenges, including resource shortages and poor management, leading to significant frustration and stress among HCWs. Working conditions were characterised by long hours and administrative burdens, contributing to physical and mental exhaustion. Psychological challenges included the impact of toxic workplace cultures and hierarchical structures, as well as the emotional toll of patient care. Despite these challenges, HCWs found a sense of purpose through patient outcomes and professional growth. However, many struggled with feelings of being stuck and employed various coping strategies, both healthy and unhealthy. The findings underscore the urgent need for systemic reforms, better resource allocation, improved working conditions, and robust support systems to enhance HCW well-being and healthcare delivery in South Africa.
A research report submitted in fulfillment of the requirements for the Master of Arts in Clinical Psychology, in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Healthcare Workers; South Africa; Subjective Experiences; South African Healthcare System; Delivery of Healthcare; Working Conditions; Psychological Impact; Burnout; Compassion Fatigue; SDG-3: Good health and well-being